Proceedings of the 2021 European Conference on Computing in Construction 2021
DOI: 10.35490/ec3.2021.203
|View full text |Cite
|
Sign up to set email alerts
|

Technology Framework for Real-Time Assessment of Spatial Conflicts in Building Retrofitting

Abstract: In the field of construction works planning, workspaces must be considered as limited resources, in the same way as labour crews and equipment. Being the work-related spatial information both contextual and affected by construction site's dynamics, a real-time management approach based on lean principles must be adopted. In this paper, a BIM-based serious game engine, framed within a high-level system architecture, is presented to enhance work progress management. The generation of a geometric model to perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The dynamic characteristics of construction site activities may be the cause of collision accidents, with construction resources often moving in situations of excessive proximity [ 8 ]. Inadequate analysis of spatial interferences in the design of construction site layouts often results in construction site spaces that are, at least temporarily, inadequate for the safe conduct of operations [ 17 , 18 ]. In addition, other factors can be identified that increase the likelihood of workers becoming victims of collision accidents: for example, the possible loss of concentration in performing daily activities due to fatigue and repetitive tasks, and the reduced visibility of construction vehicle operators due to blind spots [ 8 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic characteristics of construction site activities may be the cause of collision accidents, with construction resources often moving in situations of excessive proximity [ 8 ]. Inadequate analysis of spatial interferences in the design of construction site layouts often results in construction site spaces that are, at least temporarily, inadequate for the safe conduct of operations [ 17 , 18 ]. In addition, other factors can be identified that increase the likelihood of workers becoming victims of collision accidents: for example, the possible loss of concentration in performing daily activities due to fatigue and repetitive tasks, and the reduced visibility of construction vehicle operators due to blind spots [ 8 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%